Pengaruh Pemahaman Perpajakan, Kesadaran Wajib Pajak,Dan Kualitas Pelayanan Fiskus Terhadap Kepatuhan Wajib Pajak Dengan Sanksi Perpajakan Sebagai Variabel Moderating - Setyani Putri, Ester Yuli; Kusuma, Marhaendra; Selviasari, Rike (Jurnal Ilmiah Cendekia Akuntansi, 2022)
This study aims to determine the effect of taxpayer understanding of taxation, taxpayer awareness, and quality of tax service services on individual taxpayer compliance with tax sanctions as a moderating variable. The moderating role is to determine whether to weaken or strengthen the dependent variable and the independent variable. The objects in this study are individual taxpayers who pay SPT 2022, individual taxpayers who are obedient and timely in paying taxes in 2022, and have a TIN. The data used in this study is primary data obtained by distributing questionnaires to taxpayers who are at KPP Pratama Tulungagung. The sampling technique in this study used purposive sampling method. The number of samples taken is 150 respondents. The data analysis technique used in this research is validity test, reliability test, classical assumption test and linear regression test Moderated Regression Analysis (MRA) model using SPSS for windows. The results of this study are (1) understanding of taxation has no effect on taxpayer compliance, (2) taxpayer awareness has no effect on taxpayer compliance, (3) tax service quality has a positive effect on taxpayer compliance, (4) tax sanctions have a positive effect on taxpayer compliance, (5) tax sanctions do not moderate tax understanding on taxpayer compliance taxes, (6) tax sanctions do not moderate taxpayer awareness of taxpayer compliance, (7) tax sanctions moderate the quality of tax service services on taxpayer compliance. Kata kunci: kepatuhan wajib pajak, pemahaman perpajakan, kesadaran wajib pajak, kualitas pelayanan fiskus, sanksi perpajakan